Epigenetic regulation of bone formation - Effects of LSD1 and RCOR2 on osteoblast differentiation - Rummukainen, Petri (fi=Turun yliopisto|en=University of Turku|, 2025)
Bone remodelling is regulated by a complex network of pathways and factors where multiple cell types coordinate to maintain bone strength. Different regulatory mechanisms controlling the transcription of cell type specific genes have been previously identified. The traditional transcription regulation model has been complemented through studies on mechanisms modifying chromatin availability for transcription, called epigenetic regulation. One essential epigenetic regulator modifying the accessibility of DNA is Lysine-specific demethylase 1, LSD1. LSD1 was first found in an epigenetic regulator complex with REST corepressor 1 (RCOR1). RCOR2, a paralogue of RCOR1, was later shown to replace RCOR1 in some complexes with LSD1. LSD1 has been shown to regulate differentiation of mesenchymal and hematopoietic stem cells in vitro and in vivo. However, data on the effects of LSD1 expression or loss of function on bone tissue homeostasis are conflicting between different studies and experimental models. In this thesis, the roles of LSD1 and RCOR2 in osteoblast differentiation and function were studied using both pharmacological inhibition of LSD1 and shRNA-mediated downregulation of LSD1 and RCOR2 mRNA expression in vitro. The roles were further investigated in vivo using global and mesenchymal cell targeted conditional knockout mouse models and applying ovariectomy and closed tibial fracture healing models to highlight the effects of RCOR2 on bone formation in adult mice. Loss of LSD1 demethylation activity through pharmacological inhibition or mRNA expression led to loss of osteoblast activity both in vitro and in vivo, resulting also in the loss of growth plate chondrocyte organization and in a bone phenotype resembling osteogenesis imperfecta. The downregulation of RCOR2 in vitro led to inhibition of osteoblast differentiation, which was not replicated to the same extent in the mouse models in vivo. These results emphasize the importance of epigenetic regulation on mesenchymal cell differentiation and bone remodelling through the histone demethylation effects of RCOR2 expression and LSD1 activity. Further understanding of various epigenetic mechanisms could lead to new therapeutic approaches for bone diseases, expanding beyond the current treatment methods.

Luunmuodostuksen epigeneettinen säätely – LSD1:n ja RCOR2:n vaikutus osteoblastien erilaistumiseen Luukudoksen uudelleenmuodostusta säädellään monimutkaisella signalointireittien ja -tekijöiden verkostolla, jossa useat solutyypit toimivat yhdessä ylläpitääkseen luun lujuutta. Useita solutyypeille ominaisten geenien luentaa sääteleviä mekanismeja on tunnistettu aiemmin. Perinteistä geenien luennan säätelymallia on uuden tutkimustiedon valossa täydennetty DNA:n luettavuutta säätelevillä mekanismeilla, joita kutsutaan epigeneettiseksi säätelyksi. Yksi tärkeä DNA:n luettavuutta muokkaava epigeneettinen säätelytekijä on LSD1 (Lysine-specific demethylase 1). LSD1 tunnistettiin alun perin yhdessä RCOR1:n (REST corepressor 1) kanssa. RCOR2:n, joka on RCOR1:n geeniperheen jäsen, on osoitettu korvaavan RCOR1 joissain proteiinikomplekseissa. LSD1:n on osoitettu säätelevän muun muassa mesenkymaalisten ja hematopoieettisten kantasolujen erilaistumista. LSD1:n toiminnan tai hiljentämisen vaikutuksista luukudoksessa on kuitenkin saatu ristiriitaisia tuloksia eri tutkimusten ja koemallien välillä. Tutkimuksessamme selvitettiin LSD1:n ja RCOR2:n merkitystä luuta muodostavien osteoblastien erilaistumisessa ja toiminnassa estämällä LSD1:n aktiivisuutta ja toisaalta hiljentämällä LSD1:n ja RCOR2:n luentaa in vitro. Lisäksi käytettiin mesenkymaalisiin soluihin kohdennettuja ja kohdentamattomia poistogeenisiä hiirimalleja. RCOR2:n vaikutusta tutkittiin hiirillä myös sekä murtuman paranemisen että estrogeenivajeen aikaansaaman luunmenetyksen aikana. LSD1:n aktiivisuuden ja luennan väheneminen vähensivät osteoblastien aktiivisuutta ja luunmuodostusta, saaden lisäksi aikaan kasvulevyn rustosolujen epäjärjestyksen ja luusairaus osteogenesis imperfectaa muistuttavan luuilmiasun. RCOR2:n hiljentäminen puolestaan vähensi osteoblastien aktiivisuutta in vitro, mutta tätä vaikutusta ei nähty samassa laajuudessa poistogeenisissä hiirimalleissa. Väitöstutkimus korostaa epigeneettisen säätelyn ja erityisesti RCOR2:n ja LSD1:n tärkeyttä mesenkymaalisten solujen erilaistumisessa ja luun lujuuden säätelyssä. Epigeneettisten mekanismien ymmärtäminen voi tulevaisuudessa mahdollistaa uusien hoitomuotojen kehittämisen luusairauksien hoitoon.